Pengaruh Media Gambar terhadap Minat Belajar Siswa dalam Pelajaran IPAS tentang Tokoh Perjuangan Republik Indonesia - Murniati, Femmy; Handayani, Puji; Pertiwi, Satria; Martini, Martini; Utami, Puspa Indah; Wardarita, Ratu (ISLAMIKA, 2024)
This research is based on the fact that the learning process conducted by the fifth-grade teacher at SD Negeri 24 Sembawa, Banyuasin, still relies on the lecture method to deliver material. This type of learning leads to a lack of enthusiasm and motivation among students in participating in classroom activities. The aim of this study is to examine student engagement in learning through picture media and to assess the improvement in student learning outcomes. This research is a Classroom Action Research developed in four stages: planning, implementation, observation, and reflection. The subjects of this study were 25 fifth-grade students at SD Negeri 24 Sembawa. The type of research used is descriptive qualitative. Data collection was conducted using observation and student learning outcome tests. The results show that by using picture media, the percentage of student engagement in Cycle I was as follows: 64% (16 students) were actively involved, 24% (6 students) were passively involved, and 12% (3 students) were not involved. The percentage of student learning outcomes showed that 64% (16 students) achieved mastery, while 36% (9 students) did not. In Cycle II, the results indicated that 88% (22 students) were actively involved, 12% (3 students) were passively involved, and 0% were not involved, with the percentage of learning outcomes achieving mastery at 88% (22 students) and 12% (3 students) not achieving mastery. Although some students did not meet the expected targets, the overall percentage of success reached the predetermined target, leading to the conclusion that the research would be halted and not continued into the next cycle.